Learning From Conservation History, Future-Oriented Approaches in the Case of the Niksar Melik (Danişment) Gazi Tomb - Eski, Özge Özeke; Çobancaoğlu, Tülay (İstanbul Üniversitesi, 2025)
This article examines the Republican-era conservation history of the Melik Danişment Gazi Tomb in Niksar, one of the earliest Turkish-Islamic funerary monuments in Anatolia attributed to the Danishmendid dynasty. This study aims to illustrate how the monument’s conservation trajectory can inform future preservation policies and contribute to contemporary heritage management debates. Using archival documents, photographic evidence, and restoration documents, this study reconstructs the chronological sequence of interventions and evaluates them within the conservation paradigms and administrative frameworks of their respective periods. The findings reveal that while several restoration campaigns preserved the tomb’s structural integrity and sustained its communal function, others compromised material authenticity through undocumented additions, incompatible materials, and speculative reconstructions. Special attention is given to the 1987–1988 and 2016–2017 interventions, which introduced major design revisions that reshaped the building’s architectural expression. The surviving fifteenth-century features—including Turkish triangles, a partially preserved inscription band and original wooden shutters —represent the monument’s most authentic components. Emphasising the integration of tangible and intangible values such as ritual use, local memory, and symbolic meaning, the study advocates a holistic conservation approach grounded in critical documentation, scientific analysis, ethical decision-making, and community participation to ensure the sustainable transmission of the tomb’s historical and cultural significance to future generations.
Keywords: Architectural History; Theory and Criticism; Mimari Tarih; Teori ve Eleştiri